Analysis of Factors Causing Teachers to Be Reluctant to Become Principals in Elementary Schools - Agus Setiawan; Lud Waluyo; Iis Siti Aisyah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and analyze the factors that cause teachers to be reluctant to accept the position of principal. Methodology: The study employed a descriptive qualitative approach with a case study design involving six teachers at an elementary school in Musi Rawas. Data were obtained through in-depth interviews, non-participant observations, and document analysis. Analysis followed the Miles and Huberman interactive model, encompassing data reduction, display, and conclusion drawing. Data validity was ensured through triangulation of sources. Main Findings: The results of the study show that internal factors such as low self-confidence, time constraints, and lack of managerial experience, as well as external factors such as administrative burden, low institutional support, and an organizational culture that is not yet conducive, are the main obstacles for teachers in accepting the position of principal. Teachers also revealed that lack of role models and unclear career progression pathways became psychological barriers that affected their leadership interest. Novelty/Originality of this study: This study contributes original insights by uncovering teacher decision-making patterns in declining principal positions within rural elementary schools. It also proposes strategic, context-specific interventions to enhance teachers’ leadership readiness and support their transition into school management roles.